Actualización en el manejo del dolor agudo postquirúrgico en pacientes jóvenes sometidos a cirugía laparoscópica abdominal. - Guamani Carrillo, Katherine Morelia (2024)
The management of acute postoperative pain in young patients is a crucial aspect of recovery following laparoscopic abdominal surgery. This text aims to compile and analyze the most recent and relevant studies to identify and evaluate the most effective strategies and therapeutic approaches for controlling acute postoperative pain. The goal is to optimize available resources and improve care and clinical outcomes in this patient group. The method used was a systematic literature review with a quantitative approach. References were obtained from various databases, including SciELO, PubMed, Redalyc, and Dialnet, as well as search engines like Google Scholar and Semantic Scholar. The search and identification of texts were conducted following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) method, resulting in a final sample of 15 studies. The findings reveal that multimodal analgesia, which involves the combined use of multiple medications, is essential for effective pain management. Practical strategies were identified, such as the use of metamizole, paracetamol, and opioids, as well as intravenous infusions of opioids (oxycodone and sufentanil) administered through patient-controlled analgesia (PCA) systems. Additionally, the use of esketamine and dexmedetomidine was highlighted, as well as the implementation of regional blocks with lidocaine, ketamine, and magnesium sulfate. The insufflation of carbon dioxide and preventive analgesia were also considered relevant practices. In conclusion, the analysis of studies published in the last five years reveals a growing concern for optimizing analgesia in young patients. The findings indicate that the integration of multimodal approaches, which combine different drugs and techniques, is crucial for improving pain control and reducing opioid dependence. This review emphasizes the importance of continuing research and updating clinical practices to ensure that care is based on the latest evidence, thereby improving outcomes in managing acute postoperative pain.